2009
DOI: 10.2166/wst.2009.504
|View full text |Cite
|
Sign up to set email alerts
|

Contamination, bioaccumulation and toxic effects of perfluorinated chemicals (PFCs) in the water environment: a review paper

Abstract: Perfluorinated compounds such as perfluorooctane sulfonate (PFOS) and perfluorooctane acid (PFOA) have been recognized as emerging environmental pollutants because of their ubiquitous occurrence in the environment, biota and humans. The paper focuses on the distribution, bioaccumulation and toxic effects of PFOS and PFOA in the water. From the available literature, tap and surface water samples in several countries were found to be contaminated with PFOS and PFOA. These compounds were detected globally in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
110
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(112 citation statements)
references
References 16 publications
1
110
0
1
Order By: Relevance
“…Due to high energy of carbon-fluorine bonds, PFAAs are resistant to hydrolysis, photolysis, microbial degradation, and metabolism by vertebrates (Kissa, 2001). PFAAs, especially perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), were first reported to be widespread in the environment Kannan, 2001, 2002), and they were subsequently detected in aquatic systems (Fujii et al, 2007;Rayne and Forest, 2009) and wildlife Houde et al, 2006a;Suja et al, 2009 to bioaccumulation and biomagnification through the food chain to wildlife and humans (Loi et al, 2011;Squadrone et al, 2014). There is still long-term public concern over adverse effects of PFAAs on ecosystem and human health as well as secondary release of PFAAs from the environment (Pico et al, 2011;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high energy of carbon-fluorine bonds, PFAAs are resistant to hydrolysis, photolysis, microbial degradation, and metabolism by vertebrates (Kissa, 2001). PFAAs, especially perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA), were first reported to be widespread in the environment Kannan, 2001, 2002), and they were subsequently detected in aquatic systems (Fujii et al, 2007;Rayne and Forest, 2009) and wildlife Houde et al, 2006a;Suja et al, 2009 to bioaccumulation and biomagnification through the food chain to wildlife and humans (Loi et al, 2011;Squadrone et al, 2014). There is still long-term public concern over adverse effects of PFAAs on ecosystem and human health as well as secondary release of PFAAs from the environment (Pico et al, 2011;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These two compounds have been frequently detected in environmental samples, very often occur at the highest concentrations (So et al, 2007;Post et al, 2013), and can be found in the tissues of aquatic and terrestrial living organisms including humans (Suja et al, 2009). PFOS is the stable end product of the degradation of perfluorooctane sulfonyl fluoride (POSF) and POSF-based polymers (Giesy and Kannan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One of these chemicals, perfluorooctane sulfonic acid (PFOS), is environmentally persistent, bioaccumulative, and distributed globally [2,3]. Water is the environmental compartment of greatest concern for PFOS due to its moderate water solubility [4]; therefore, assessing the potential risks of PFOS in the aquatic environment is necessary. An important step in ecological risk assessment is to determine the low-risk concentration below which adverse effects on the ecosystem are acceptable.…”
Section: Introductionmentioning
confidence: 99%